(untitled) (Menara Perkebunan, 2016)
Summary Tissue culture technique for arabica coffee faces some problems, mainly in plantlets regeneration from cultured explants. The objectives of this experiment were to examine the effect 2,4-D and 2-ip combinations on somatic embryogenesis and regeneration of arabica coffee from several different explants. Basal medium used in this experiment was MS medium with ½ concentration of macro and micro salts. Experiment to induce primary somatic embryos (SE) was arranged in factorial randomized complete design with 10 repeats. The first factor was the type of explants, leaf, epicotyl, hipocotyl and root explants. The second factor was plant growth regulator i.e. combination of 1  M 2,4-D with 5, 10, 15, 20  M and combination of 5  M 2,4-D with 5, 10, 15 and 20  M 2-ip. To multiply SE, secondary SE was induced from primary SE on medium containing combination of 0.6  M IAA and 13.3; 17.8 and 22.2  M BAP. Cotyledonary SE were germinated on media containing GA 3 (0, 5, 10 and 15  M), and then regenerated on medium free of growth regulator. Plantlets with 4-5 leaf pairs were transfered into the soil medium for acclimatization. The results show that primary SE can be induced from all explants with the highest frequency on medium containing 1  M 2,4-D and 15  M 2-ip. Induction of primary SE, in leaf explant was more effective than other explants. Medium containing 0.6  M IAA and 22.2  M BAP gave the highest percentage of SE multiplication i.e. 52.6% with average SE number of 6.25. Plantlets regeneration can be conducted by culturing SE on maturation medium free of growth regulator for one month followed by germinating on medium containing GA 3 , and then culturing on medium free of growth regulator again. The highest percentage of germinated embryos was obtained after three weeks and six weeks cultured in the medium containing 5  M GA 3 , i.e 49% and 90.15 respectively. From total plantlets obtained, 75% of them were normal. Sixty percents of the young plants grew well in the greenhouse. Ringkasan Teknik kultur jaringan tanaman kopi arabika masih menghadapi beberapa kendala terutama pada tingkat regenerasi planlet dari eksplan yang dikulturkan. Penelitian ini bertujuan untuk mengetahui pengaruh kombinasi 2,4-D dan 2-ip terhadap embriogenesis somatik dan regenerasi kopi arabika dari berbagai eksplan. Media dasar yang digunakan adalah medium MS ½ konsentrasi garam makro dan mikro. Percobaan induksi embrio somatik (ES) primer disusun menurut rancangan acak lengkap faktorial dengan 10 ulangan. Faktor pertama adalah jenis eksplan, erdiri atas daun, epikotil, hipokotil dan akar in vitro. Faktor kedua adalah zat pengatur tumbuh, yaitu kombinasi 1 M 2,4-D dengan 5, 10, 15 dan 20M 2-ip, serta kombinasi 5 M 2,4-D dengan 5, 10, 15 dan 20 M 2-ip. Untuk mem- perbanyak jumlah ES yang didapatkan, dilakukan induksi ES sekunder dari ES primer pada medium yang mengandung kombinasi 0,6 M IAA dan 13,3; 17,8 dan 22,2 M BAP. ES fase kotiledon kemudian dikecambahkan pada medium yang mengandung GA 3 (0, 5, 10 dan 15 M) dan selanjutnya diregenerasikan pada medium tanpa zat pengatur tumbuh. Planlet yang mempunyai 4-5 pasang daun dipindahkan ke medium tanah untuk aklimatisasi. Hasil yang diperoleh menunjukkan bahwa ES primer dapat diinduksi pada semua eksplan yang digunakan dengan frekuensi tertinggi pada medium yang me- ngandung 1 M 2,4-D dan 15 M 2-ip. Induksi ES primer pada eksplan daun lebih efektif dibandingkan eksplan lainnya. Untuk per- banyakan ES, medium yang mengandung IAA 0,6 M dan BAP 22,2 M memberikan persentase tertinggi pembentukan ES sekunder yaitu 52,6% dengan rata-rata jumlah ES 6,25. Regenerasi planlet dapat dilakukan dengan mengkulturkan ES pada medium maturasi tanpa zat pengatur tumbuh selama satu bulan, kemudian dikecambahkan dalam medium yang mengan- dung GA 3 , dan selanjutnya dipindah ke medium tanpa zat pengatur tumbuh kembali. Perkecambahan ES tertinggi diperoleh pada medium dengan penambahan GA 3 5 M yaitu 40,9% setelah tiga minggu dan 90,1% setelah enam minggu. Dari total planlet diperoleh 75% planlet normal. Hasil aklimatisasi menunjukkan bahwa 60% bibit mampu bertahan di rumah kaca.